Gender Preference in Current Pregnancy among Primigravidae - Thapa, Meena; Bajracharya, Junu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study preference of gender of fetuses in present pregnancy, wish of number of children in the family, and knowledge of pre-natal sex selection by the pregnant women, and to study the impact of education level of women on preference of fetal gender and the desire of women to know the gender of fetuses. Methods: It was a descriptive study done in Obstetrics and Gynaecology Department of Kathmandu Medical College. All primigravidae, who did not know the gender of their fetuses and willing to participate in the study were enrolled in the study. The pregnant women were interviewed regarding demographic profile of the women, choice of gender of fetuses, number of children they want to have and knowledge regarding prenatal sex selection, using semi structured questionnaire. Results: Two hundred women were studied. Two third of them were educated minimum of 12th Class. Most of the pregnant women (81%) did not show preference of gender of their fetuses, only 13% of them wanted to have son in this pregnancy. About 61% of them want to have two children in their family. Regarding prenatal sex selection, only 44% knew about it. More than half (56%) of the women showed interest in knowing the gender of fetuses in present pregnancy. The education status of women did not have an effect on the choice of either gender or wish to know the gender of unborn fetuses by primigravidae. Conclusions: Most of the primigravidae had no choice of gender of fetuses. Two children in the family was regarded as ideal by most of the women